Climate change adaptation across the life-course - from pregnancy to adolescence – it's time to advance the field of climate change and child health. (1st June 2023) - Helldén, Daniel; Ndejjo, Rawlance; Sturm, Amanda; Persson, Ida; Wanyenze, Rhoda; Ebi, Kristie L; Nilsson, Maria; Alfvén, Tobias
Abstract: Children are bearing and will continue to bear a high burden from climate change, through direct and indirect pathways. Climate change adaptation interventions are essential to limit the current and projected impacts of climate change on child health. However, the perspective of children and their health with regards to adaptation in research and policy is limited. Ensuring that adaptation interventions are context specific, consider interrelated barriers to implementation and leverage existing structures including multisectoral collaboration is vital. Further, a life-course perspective on child health and well-being could serve as a template for tailoring adaptation interventions to the specific vulnerabilities and needs of specific development periods of the child. A meaningful engagement of children and young persons in the design and implementation of adaptation interventions is essential to increase effectiveness and uptake. With climate change effecting millions of children worldwide, it is high time to put child health at the center of adaptation.